A Tale of Two Cultures. (2nd July 2016) - Knight, David
Abstract : My life has been framed by the two-cultures debate. A scientific education, good but narrow, led me into history of science just as anxiety about specialisation opened opportunities for 'bridge' subjects, and History and Philosophy of Science seemed just that bridge. My DPhil thesis (1964), on the reception of chemical atomic theory in the nineteenth century, led to a new lectureship at Durham that involved giving courses right across the different faculties, and close, stimulating involvement with other institutions where it was also being taught and researched; with the business of examining, reviewing, editing, and publishing; with the various societies set up to promote history of science; and with scientific societies like the Royal Society, the British Association for the Advancement of Science, and the Royal Society of Chemistry, finding science losing public esteem, and becoming interested in their past and how it might promote understanding and enthusiasm in the present. Encounters with historians of science, technology, and medicine at home and abroad, with coal miners and with museum curators, all wrestling with very different histories, indicated that Snow's 'two cultures' were a feature especially of 1950s Britain, that cultures were deeply divided in all sorts of ways, and that the social history of science was as important as its intellectual history. So over time I found myself teaching course s, and writing, on science and religion in the nineteenth century as well as on Butterfield and Hall's 'Scientific Revolution' that had dominated the subject in the 1960s and the 'Second Scientific Revolution' that had excited young Turks of my generation. Finally, I launched a course on Two Cultures as a historical phenomenon, focussing upon science, its developing institutions, reception, and place in the culture of the nineteenth-century Age of Science.